Generalized (ℱ,b,φ,ρ,θ)-univex n-set functions and global semiparametric sufficient efficiency conditions in multiobjective fractional subset programming - G. J. Zalmai (International Journal of Mathematics and Mathematical Sciences)
A fairly large number of global semiparametric sufficient efficiency results are established under various generalized (ℱ,b,φ,ρ,θ)-univexity assumptions for a multiobjective fractional subset programming problem.